Welfare state retrenchment: the partisan effect revisited - Bruno Amable; Donatella Gatti; Jan Schumacher (Institute for the Study of Labor (IZA), 2006)
This paper aims to shed light on the role of the 'ideology' of political parties in shaping the evolution of the welfare state in 18 developed democracies, by providing empirical findings on the determinants of social programs entitlements and social spending over the period 1981-1999. The paper shows that structural change is a major determinant of the extent of social protection. Our results suggest that overall spending is driven up by structural change. On the other hand, strong structural change has a negative influence on welfare entitlements measured by net replacement rates of sickness insurance or unemployment benefits. Partisan influence plays an important role in the dynamics of the welfare state. Left-wing governments strengthen the positive effect of shocks on aggregate social expenditure while right-wing governments undertake even stronger cutbacks in replacement rates as a reaction to structural change.
Keywords: H5; I1; J8; 330; welfare state; ideology; structural change